Senior High School Students’ Lack of Truth-Seeking Behavior in Mathematics Problem Solving - Rahmawati, Mira; Kurniati, Dian; Kristiana, Arika Indah; Susanto, Susanto; Alfarisi, Ridho; Osman, Sharifah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
The objective of this study is to discern the patterns of truth-seeking behaviors among students when tackling mathematics problems involving an unknown universe of discourse. Employing a qualitative descriptive approach, the research encompassed stages including instrument preparation and validation, data collection from two mathematics problems with no specified universal set, subject selection, data analysis, triangulation, and interpretation. The research group consisted of tenth-grade high school students who were considered to have ideal abilities in problem-solving. The instrument used was valid and reliable. The findings reveal that students tend to exhibit a lack of truth-seeking behavior when tackling problem-solving tasks. These behaviors include: (1) verifying the universal set, (2) articulating and defining the universal set, (3) documenting the formulas used to solve problems according to the objectives, (4) outlining the steps employed, (5) working through the questions in accordance with predetermined steps, and (6) evaluating the outcomes obtained to ensure their alignment with the established objectives. Their behavioral patterns unfold as follows: (1) comprehending questions to extract problem details and jotting down pertinent information during the problem identification phase, (2) identifying and documenting the queries posed in questions during the goal-setting stage, (3) utilizing all established information during the strategy implementation phase, and (4) formulating conclusions and conducting result verification during the review and evaluation stage. Future researchers can develop learning methods to familiarize students with truth-seeking behaviors.